A new solar powered species of the genus Phyllodesmium Ehrenberg, 1831 (Mollusca: Nudibranchia: Aeolidoidea) from Indonesia with analysis of its photosynthetic activity and notes on biology - Burghardt, Ingo; Wägele, Heike (Zootaxa, 2004)
A new Phyllodesmium species, P. jakobsenae nov. sp., is described from North Sulawesi, Indonesia. The new species is associated with the octocoral Xenia sp. Its external morphology is similar to other Phyllodesmium species inhabiting Xenia colonies, especially to P. hyalinum Ehrenberg, 1831, but cerata morphology and color, tooth and jaw morphology as well as the digestive glandular branching system within the cerata clearly distinguishes this new species. Behavioural notes are given and spawning is described. Active photosynthesis due to zooxanthellae (Dinophyceae of the genus Symbiodinium) in the digestive gland was measured in situ with a Diving-PAM (Pulse Amplitude Modulated Fluorometer). Experiments with P. jakobsenae indicate a symbiotic relationship with zooxanthellae at least for some days. These results are discussed in comparison to another Xenia inhabiting species, Phyllodesmium crypticum Rudman, 1981. Histological investigation of the digestive diverticula within the cerata of the new species also indicate a high effectiveness of the symbiosis.